An Effective Load Balancing In Long Term Evaluation Self Optimization Network Using Multi Objective Optimized Algorithm (International Journal of Engineering and Computer Science, 2015)
A self-optimizing network is an effective method for network management and maintenance in Long TermEvolution, which supports the co channel deployed heterogeneous networks and significantly increases the quality of service.The Zone based Load Balancing uses several game theoretic approaches to carry out load balancing but it results inuncoordinated load distribution among multiple cells. It may cause the problem of hidden cell case and slow convergenceissues. Along with this problem the Nash Equilibrium used in game theory algorithm cannot be obtained, it may continuouslyfinding solution for long duration. It can be solved by introducing the innovative method of meta heuristic search algorithmcalled Multi objective Bat Algorithm. It is very promising and could outperform the existing algorithms. The Multi ObjectiveBat algorithm combined with the priori expert knowledge reduces search space and computational time required for designingthe MLB controller. The Multi Objective Algorithm provides the best optimization solution in short period of time and theproblem of slow convergence time gets eliminated.